The altar as central symbol in rites and velorios (Dissertare, 2017)
In the culture of the people, there are elements that are inseparable from the social and religious fact. This is represented by the popular religious celebrations that have been handed down from generation to generation. These celebrations contain forms of social and religious organization that define and make them have presence in front of the changes without losing their essence. The purpose of this production is to highlight the use and importance of the altar as a central element in the velorios that in honor to the saints, and dead people are celebrated throughout the venezuelan territory, as well as the role of Singers or Promoters of Canturías, as transmitters of the cultural legacy of the nation. The methodological route followed to carry out this study was mainly guided by a review of bibliographic sources containing information about the use and importance of the altar from the religious rites of the Sumerian civilization to the Velorios that are part of the religious festivals of the Lara State. Finally, the role of the altar in the popularization of rituals and the importance of popular singers as transmitters of the cultural heritage of the people is highlighted.
Keywords: altar; culture; religiosity popular celebrations